Pietisme dalam Pendidikan Agama Kristen: Pembentukan Kesalehan Pada Remaja di Era Digital - Puja Devi Sri Raso Tampubolon; Chrismas Febe Wulandari; Sudiarjo Purba (Jurnal Shanan, 2022)
The formation of pietism refers to the warmth of faith, piety, and the personal experience of God's salvation. In particular, pietism is a concern for parents, schools and churches to address the social problems of teenagers: spending time playing games, low interest in reading the word, and fellowship with God. It causes the value of love to be low and it is easy to commit cyberbullying crimes. This study aims to analyze pietism in Christian religious education: the formation of piety in adolescents in the digital era. The research method used is qualitative research, with a literature study approach. This paper is a study of the pietism movement in Christian religious education in families, schools and churches. The results of this study are, parents, schools and churches form pietism in adolescents based on Christian values with an understanding of pietism, the impact of the digital era for adolescents, and the formation of pietism through the application of various programs in families, schools and churches.